Anefficient 2-Step DNA symmetric cryptography algorithm based on dynamic data structures - P. George, Jossy; Varghese Kureethara, Joseph (International Journal of Engineering and Technology, 2018)
The security of text has become highly demanding in today’s fast growing networking world. DNA computing is one of the emerging technologies in the arena of huge data storage and parallel computation. A single gram of DNA holds 5.5 petabytes of data. This leads to the increased risk in data communication. DNA in computers is mapped to human genome. Thus, the sequence of nucleotide base constructs the foundation of uniqueness. In this paper, a new scheme acronymed as –‘Cryptography on DNA Storage’-CDS is provided. It performs the DNA data encryption in just two-step by using random private key for each letter in the plaintext and parallel swapping of the resultant text in small clusters. It is discussed keeping the time and space complexity of the algorithm in concern.